Evaluating the effectiveness of the logistics system on company perfomance: a case study of Grain Marketing Board - Saruchera, Rufaro (Midlands State University, 2017)
The research study was focused on evaluating the effectiveness of logistics system on company performance. The key objectives of the study were to identify the effects of availability of transportation on sales volume, to determine the effects of order processing on service quality and to establish the effects of packaging on brand image. Literature from different authors on the logistics system, components of logistics system (packaging, order processing and transportation) was reviewed. The researcher used a sample size of 43 respondents comprising of GMB management, employees and business customers. The study was stemmed from slow order processing, too much breakages and slow deliveries on distribution by GMB. The researcher used interviews and questionnaires to collect and gather data that was relevant to answer the problem of the study. The respondents were selected using non probability sampling techniques namely judgmental sampling and convenience sampling. The research outcomes exposed that the company performance can improve if the logistics system is effective. The researcher recommended the company to stock all Silo products, secure more logistics trucks and heavily distribute its products in different locations on time and to network all of its depots on the SAP system and retrain its employees on how to use SAP system. Area of further studies was also given by the researcher.